Isokinetic profiling of elite youth footballers: informing selection of a practicable and efficacious isokinetic screening test - Horn, T.; Brogden, C.; Greig, M. (Research in Sports Medicine, 2023)
Isokinetic dynamometry represents the clinical gold standard for strength assessment but testing lack consensus. Elite youth male football players (n = 28) completed 20 repetitions (analysed as four epochs) of eccentric knee flexor (eccKF) and concentric knee extensor (conKE) trials at 60, 180 and 270°·s-1, quantifying peak torque (PT) and functional range (FR). There was a significant (P < 0.001) main effect for fatigue and angular velocity in conKE PT; eccKF PT was not significant across epoch (P = 0.35) and velocity (P = 0.12) and a velocity x epoch interaction highlighted more repetitions were required to elicit fatigue as velocity increased. FR decreased with fatigue (P < 0.001) and velocity (P < 0.01) in conKE and eccKF, indicative of a narrowing of the strength curve. Clinical interpretation advocates an isokinetic test comprising at least 15 reps at a velocity = 180°·s-1 and analysis beyond the peak of the strength curve (PT) to inform clinical reasoning and individualized exercise prescription.